AUTHORITATIVE PARENTING PRACTICES DAN PRESTASI BELAJAR SISWA SMA DI BANDA ACEH - Anggraini, Zirlia; Ridha, Usfur (Jurnal Psikologi, 2017)
Academically, the bencmark of successful person is learning achievement which is involved by internal and external factor. One of the external factor that involved students learning achievement is authoritative parenting practices. It is kind of parenting authoritative done by parents in achieving certain purposes, including learning achievement. Including parents in the students instructional process can create a good atmosphere such acceptance or warmness, supervision, and psychological autonomy granting. The sampling technique used was multistage cluster and stratified random sampling. The participants was 334 students (145 males and 189 females). The instrument of this research is adapted from Authoritative Parenting Practices Scale which consists of 26 items, and learning achievement by using the mean of studentsâ€™ record. The result of data analysis by using Pearson correlation technique showed that was the positive and significant correlation between authoritative parenting practices and students learning achievement in Banda Aceh (r= .309; p< .001). It indicates that the higher authoritative parenting practicesaccepted by the students, the learning achievement increase or vive versa. It can be concluded that parents have the important role in achieving students learning achivement.Â